The Effect of Lower Limb Drop Knee Jump and Box Jump Plyometric Training Methods on Mawashi Geri Kick Speed in Junior Karate Athletes - Nurtafajti, Aira Septia; Sagitarius, Sagitarius; Novian, Geraldi (Indonesian Journal of Physical Education and Sport Science, 2025)
Study Purpose. The background of this study is the low kicking speed of several junior karate athletes, which impacts the effectiveness of attacks during competition. The aim of this study is to improve the kicking quality, specifically the speed of the mawashi geri kicks of junior karate athletes. Materials and Methods. The research method used was an experiment with a two-group pretest-posttest design. The research sample consisted of 10 junior karate athletes with an age range of 15-17 years who were divided into two groups, namely the knee jump training group and the box jump training group . The research instrument used was a mawashi geri kick speed test by recording the time needed to perform three kicks as quickly as possible. The tools needed include a stopwatch, a meter, and a punching bag. The data were analyzed using a normality test, a homogeneity test, a paired sample t-test, and an independent sample t-test. Results. The average percentage increase in the knee jump group was 11.84%, while the box jump group increased by 6.64%, with an overall average increase reaching 9.24%. The results of the paired sample t-test showed a significant difference between the pretest and posttest results (p <0.05), while the results of the independent sample t-test showed no significant difference between the two methods (p>0.05). Conclusion. Thus, it can be concluded that plyometric training, both bent knee jumps and box jumps, is effective in increasing the speed of mawashi geri kicks in junior karate athletes. However, bent-knee jumps yielded greater average gains than box jumps, as the coordination of the knee-to-chest jump is considered to best align with the characteristics of the mawashi geri kick technique.